Atmospheric wet deposition of trace metals in the Suwon region in Korea during farming periods. (2016) - Kim, Min-Kyeong; Jung, Goo-Bok; Lee, Jong-Sik; Jeon, Hyun-Jung; Kim, Myung-Hyun; Kim, Min-Young
This study investigated the characteristic distributions of heavy metals in rainwater, and the relationship between the concentrations of heavy metals and other chemical properties of the rainwater was also evaluated. Chemical properties of the rainwater varied between different raining periods and years. The volume-weighted mean of rainwater pH ranged from 3.9 to 6.7, and the individual volume-weighted means followed the order Zn > Pb > Cu > Cr > Ni > Cd. There were positive correlations between the major ionic components, such as Ca, Mg, and K, and the heavy metal concentrations of rainwater. The trends of monthly heavy metal concentrations showed higher values in July during 2011-2013. The order of average enrichment factors (EFs) was Cd > Pb > Cu > Zn > Ni > Cr; all of these were relatively higher than the EFs of natural components such as Fe, Mg and Ca. The overall finding of this study indicated that the concentration of dissolved trace metals can increase under the condition of acid rain.